Clinical research on COVID-19: perceptions and barriers to participation in The Gambia. Issue 2 (21st February 2022) - Diallo, Brahima Amara; Usuf, Effua; Ceesay, Omar; D'Alessandro, Umberto; Roca, Anna; Martinez-Alvarez, Melisa
Abstract : Introduction: The need to rapidly identify safe and efficacious drug therapies for COVID-19 has resulted in the implementation of multiple clinical trials investigating potential treatment options. These are being undertaken in an unprecedented research environment and at a higher speed than ever before. It is unclear how West African communities perceive such activities and how such perceptions influence participation in COVID-19 clinical trials. This qualitative study was conducted to assess the level of acceptability of a clinical trial on the prevention and treatment of COVID-19 in The Gambia and identify strategies to better engage communities in participating in such a trial. Methods: Data were collected using digitally recorded semistructured interviews (SSIs) and focus group discussions (FGDs) in Brikama and Kanifing local government areas. These are two of the most densely populated administrative subdivisions in The Gambia, where the clinical trial was to be implemented by the MRC Unit The Gambia. 26 men and 22 women aged between 19 and 70 years, with diverse socioeconomic profiles, participated in 8 FGDs (n=36) and 12 SSIs (n=12). Thematic analysis was used to analyse the data. Results: Fear of stigmatisation of patients with COVID-19 was a recurring theme in most FGDs and SSIs, with detrimental effects on willingness to accept COVID-19 testing and home visits to follow up patients with COVID-19 and their household contacts. Preserving the privacy of individuals enrolled in the study was key to potentially increase trial participation. Trust in the implementing institution and its acknowledged expertise were facilitators to accepting the administration of investigational products to sick individuals and their close contacts. Conclusion: COVID-19 is a stigmatising disease. Developing a research–participant collaboration through an ongoing engagement with community members is crucial to a successful enrolment in COVID-19 clinical trials. Trust and acknowledged expertise of the implementing institution are key facilitators to foster such collaboration.